2007
DOI: 10.1111/j.1600-0838.2007.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

A social cognitive approach to burnout in elite athletes

Abstract: The purpose of this study was to investigate athlete burnout from a social-cognitive perspective by examining the relationship between social cognitive motivational variables at the start of a season and signs of burnout in elite athletes at the end of the season. Participants were 141 (F=60, M=81) elite winter sport athletes competing in Alpine skiing, Biathlon, Nordic Combined, Nordic skiing, and Speed skating. Participants completed a comprehensive motivation assessment package at the start of the season an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
149
2
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(175 citation statements)
references
References 51 publications
(86 reference statements)
13
149
2
8
Order By: Relevance
“…First, they corroborate previous findings that perfectionism in athletes is closely associated with performance goal orientations (Dunn et al, 2002;Hall et al, 1998;Lemyre et al, 2008;Ommundsen et al, 2005). Second, they show that it is important to differentiate between perfectionistic strivings and perfectionistic concerns as well as between approach and avoidance orientations.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…First, they corroborate previous findings that perfectionism in athletes is closely associated with performance goal orientations (Dunn et al, 2002;Hall et al, 1998;Lemyre et al, 2008;Ommundsen et al, 2005). Second, they show that it is important to differentiate between perfectionistic strivings and perfectionistic concerns as well as between approach and avoidance orientations.…”
Section: Introductionsupporting
confidence: 79%
“…In particular, perfectionistic strivings may not capture perfectionistic personal standards which are a defining characteristic of perfectionistic strivings dimension, and negative reactions may not capture perfectionistic concerns over mistakes which are a defining characteristic of the perfectionistic concerns dimension (see Stoeber & Otto, 2006). Moreover, except for Stoeber et al's (2008) study, all previous studies on perfectionism and achievement goals have included personal standards and concern over mistakes (Dunn et al, 2002;Hall et al, 1998;Lemyre et al, 2008;Ommundsen et al, 2005). Consequently, it would be important to include perfectionistic personal standards and concerns over mistakes when investigating the relationship between perfectionistic strivings, perfectionistic concerns, and achievement goals.…”
Section: Introductionmentioning
confidence: 95%
“…Empirical evidence suggests that negative dimensions of perfectionism may be critical antecedents of burnout in young athletes Lemyre et al, 2007). However, because few studies have systematically examined the nature of the relationship between perfectionism and burnout in elite youth sport, the present investigation sought to extend research in this area by examining potential psychological mechanisms that would help explain why perfectionistic athletes may be vulnerable to the experience of this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…While there has been little empirical examination of the relationship between perfectionism and athlete burnout, current findings suggest that specific maladaptive dimensions of perfectionism appear to be the critical antecedents of the syndrome Lemyre et al, 2007). However, this research has relied exclusively on a measure of perfectionism developed by Frost and colleagues (FMPS;Frost et al, 1990).…”
Section: Introductionmentioning
confidence: 95%
“…Miller & Kerr (2002) alluded to this imbalance when they suggested that performance excellence is often at the expense of personal DYNAMIC BALANCE, CORRECTION THEORY 11 excellence, compromising the development of the whole person, and arguably increasing the likelihood of athlete burnout and/or psychopathology. This imbalance has also been considered within research investigating the deleterious effects of perfectionism in sport (e.g., Gould, Udry, Tuffey, & Loehr, 1996;Lemyre, Hall, & Roberts, 2008). What hasn't been considered is the possibility that notions of balance and imbalance, in relation to a dynamically balanced system, might provide a new theoretical framework to help develop our understanding of performance variation and peak performance in sport.…”
Section: Balance and Sport Performancementioning
confidence: 99%